KEMAMPUAN ARUS KAS DAN LABA DALAM MEMPREDIKSI ARUS KAS MASA DEPAN - Laksmi, Indira; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2014)
Cash flow prediction is obliged to value the company abilty in making future cash flow. The purpose of the research is to know the different between capability of operating cash flow and net income to assume of future cash flow in consumer goods company. Forecast error is used to evaluate prediction capability. Sample is determine by purposive sampling method, so that 46 sample will be acquire. This research using two years prediction. The operating cash flow and net income 2005-2010 is used to predict cash flow in 2011, and operating cash flow and net income 2006-2011 is used to predict cash flow in 2012. Analysis technic is being used independent t-test. The result is operating cash flow have not difference capability than net income to predict future cash flow of consumer goods company.
Keywords: cash flow, operating cash flow, net income, future cash flow